2013
DOI: 10.1213/ane.0b013e3182908d5d
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Ultrasound-Guided and Landmark-Based Approaches to Saphenous Nerve Blockade

Abstract: In our prospective study, we have demonstrated that ultrasound-guided above the knee saphenous nerve blocks have higher success rates than a below the knee field block and are easily performed in a short amount of time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 18 publications
0
32
0
1
Order By: Relevance
“…However, two subsequent trials did report improved success rate with the transsartorial approach (with LOR or US) compared to blind LA infiltration distal to the knee (80%–100% vs 30%–40%; p<0.05) 126 129. In recent years, the US transsartorial approach has also been compared to US-guided LA injection between the sartorius and vastus medialis muscles proximal to the knee joint with mixed results: one trial found no intergroup differences in terms of success rate129 while the other RCT reported a higher success rate (100% vs 86%; p=0.003) and shorter onset time (3 vs 9 min; p<0.001) with the transsartorial approach 130…”
Section: Nerve Blocks Of the Lumbar Plexusmentioning
confidence: 99%
“…However, two subsequent trials did report improved success rate with the transsartorial approach (with LOR or US) compared to blind LA infiltration distal to the knee (80%–100% vs 30%–40%; p<0.05) 126 129. In recent years, the US transsartorial approach has also been compared to US-guided LA injection between the sartorius and vastus medialis muscles proximal to the knee joint with mixed results: one trial found no intergroup differences in terms of success rate129 while the other RCT reported a higher success rate (100% vs 86%; p=0.003) and shorter onset time (3 vs 9 min; p<0.001) with the transsartorial approach 130…”
Section: Nerve Blocks Of the Lumbar Plexusmentioning
confidence: 99%
“…58.6 ) Pes anserinus bursitis Tenderness more distal over the pes anserinus (see Fig. 58.6 ) Medial collateral ligament (MCL) injury Medial instability, pain with valgus movement Hip joint pathology [ 19 ] X-rays and MRI will show pathology be diffi cult to locate [ 46 ]. Others describe using the plane between the sartorius and vastus medialis muscles [ 47 ] ( Fig.…”
Section: Sartorial Tendonitismentioning
confidence: 99%
“…Others describe using the plane between the sartorius and vastus medialis muscles [ 47 ] ( Fig. 58.19 ), although this plane may be diffi cult to locate in obese patients [ 46 ]. The superfi cial femoral artery in the mid-proximal femur may provide a landmark that is reliable across a range of providers and patients [ 46 , 48 ].…”
Section: Sartorial Tendonitismentioning
confidence: 99%
See 2 more Smart Citations